2019
DOI: 10.1016/s2352-3026(19)30014-6
|View full text |Cite
|
Sign up to set email alerts
|

High cutoff versus high-flux haemodialysis for myeloma cast nephropathy in patients receiving bortezomib-based chemotherapy (EuLITE): a phase 2 randomised controlled trial

Abstract: Background In multiple myeloma, severe acute kidney injury due to myeloma cast nephropathy is caused by pathogenic free light chain immunoglobulin in serum. High cutoff haemodialysis (HCO-HD) can remove large quantities of free light chain immunoglobulin from serum, but its effect on clinical outcomes is uncertain. We therefore aimed to assess whether HCO-HD could increase the frequency of renal recovery in patients with de novo multiple myeloma, severe acute kidney injury, and myeloma cast nephropathy relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 33 publications
2
130
0
2
Order By: Relevance
“…Treatment of MM with bortezomibbased regimens became increasingly common after 2008 and the evidence in clinical and epidemiological studies for patients with MM and RI supports the benefits of this treatment 30,48 . The lack of association with extracorporeal removal of FLC is consistent with the major randomised controlled trials for plasma exchange and HCO-HD.in patients with MM and AKI 46,50,51 .…”
Section: Discussionsupporting
confidence: 71%
“…Treatment of MM with bortezomibbased regimens became increasingly common after 2008 and the evidence in clinical and epidemiological studies for patients with MM and RI supports the benefits of this treatment 30,48 . The lack of association with extracorporeal removal of FLC is consistent with the major randomised controlled trials for plasma exchange and HCO-HD.in patients with MM and AKI 46,50,51 .…”
Section: Discussionsupporting
confidence: 71%
“…Two controlled trials in which all patients received a bortezomib-based multiple myeloma treatment showed no differences in the primary outcome of dialysis independence between the groups randomly assigned to receive high-cutoff hemodialysis and standard of care (high-flux hemodialysis). 17,18 Because of more effective chemotherapy and better supportive care, survival has improved for patients with multiple myeloma who need dialysis upon presentation, but the reduction in circulating FLCs still requires time, allowing the progression of kidney disease, which may occur rapidly. A deeper understanding of the monoclonal FLC-mediated mechanisms that lead to kidney injury may help in improving care.…”
Section: How Does This Study Compare With Prior Studies?mentioning
confidence: 99%
“…Furthermore, in a recent randomized clinical trial involving 98 patients with myeloma cast nephropathy on chemotherapy, the use of HCO hemodialysis compared with conventional hemodialysis did not result in a significant benefit with respect to hemodialysis dependence at 3 months [16]. Later, Hutchison et al shown that HCO hemodialysis was not associated with an improvement in renal recovery as compared with to High Flux-hemodialysis in patients with a new diagnosis of MM and myeloma cast nephropathy who received modified-dose bortezomib-containing chemotherapy although in both groups there was a sustained early reduction in serum FLC levels [17].…”
Section: Introductionmentioning
confidence: 97%